Posted by CHLOE on Wednesday, December 19, 2012 at 6:13am.
by fg I assume you mean f*g
f*g = (x^2+3)*(2x+1) = 2x^3 + x^2 + 6x + 3
g=2x+1, so g^-1 = (x-1)/2
so, if f = 12 g^-1,
x^2+3 = 12 * (x-1)/2
x^2+3 = 6x-6
x^2 - 6x + 9 = 0
(x-3)^2 = 0
x = 3
Thank you steve
It says i need to find f(g), i got a different result for some reason help please!
And also in the second part, how did you get g^-1 = (x-1)/2
Thank you steve x
That's because fg is ambiguous. I did f(x) * g(x).
f◦g = f(g) = g^2+3 = (2x+1)^2+3
= 4x^2 + 4x + 4
to get g^-1, just solve for x
g = 2x+1
g-1 = 2x
x = (g-1)/2
then switch variables, and g^-1 = (x-1)/2
Is there any reason why f(g)=g^2+3
why do we replace the x with g?
Sorry steve im trying my hardest to understand this
Calculus - We're learning about different kinds of functions and I don't...
Maths - Thanks guys for your response!!!! x I have another one. If the two ...
maths - I am really facing difficulty in maths. I do my best to improve in maths...
Maths - Thanks steve for a brilliant answer! Got one last one which is ...
Maths - I have a test tomorrow and I really don't get this, please help me...
maths - the functions f and gare defined by f(x)=2/(x+1), x>0 g(x)=1-x^2...
Algaebra - Two functions f and g are defined by f:x = x^2 + 3 g:x = 2x+1 Find ...
mega urgently important maths - the functions f and g are defined by f(x)=2/(x+1...
Maths-algebraic expression - Using suitable identities evaluate (z-14)(z-1) ...
Maths - Hey :) I'm sitting my maths non-calculator GCSE tomorrow and am ...
For Further Reading